Mathematical Modeling and Optimization of Water Efficiency in Residential Buildings - Amin, Mahmoud (AUC Knowledge Fountain, 2022)
Water scarcity is a global issue that is rapidly worsening. The domestic sector is one of the fastest-growing segments of world water usage. Many researchers have explored various approaches to promote sustainable uses of water, with Greywater (GW) recycling and utilization of innovative plumbing fixtures among the methods presented to reduce freshwater consumption for domestic usage. Nonetheless, previous studies have dealt with both means independently, with limited analysis of the integrated effect of utilizing GW recycling with innovative plumbing fixtures, both on quality of supplied water, as well as on cost of the integrated system. Accordingly, this research aims at improving the efficiency of water usage in residential buildings, through the development of a mathematical optimization model that utilizes a comprehensive database in order to select the most appropriate GW recycling system, plumbing fixtures, and system components with the aim of improving water quality, minimizing water usage and reducing cost. The developed model is divided into three main modules: inputs, water flow, and annual worth quantification. The user is required to specify certain inputs that define parameters related to the building, its surrounding landscape, as well as economical parameters. Based on such information, the model determines the suitable fixtures’ types for each water appliance, and the feasibility of utilizing GW recycling along with determining; the water source to be recycled and the treatment system type to be used, with the objective of minimizing both the total annual worth and the utilized potable water quantity. The model was verified on a case study and sensitivity analysis was performed to explore the impact of changing major input factors on the total annual cost. A factorial design examining both two and three-factor interactions was used. The number of residents and the annual increase of water tariffs factors showed the most significant impact on the total annual worth accounting for 55% and 43.7% of total variability, respectively. Furthermore, The model was validated by comparing its results with a previous study conducted in the United Kingdom, where the developed model led to a significant reduction in the lifecycle cost of the decentralized water system in residential buildings and attained freshwater savings of 58.17%.